Is Regular Visiting Associated with Lower Costs? Analyzing Service Utilization Patterns in the First Nations Population in Canada - James L. Leake, MSc, DDS; Stephen Birch, DPhil; Patricia A. Main, MSc, DDS; Elsa Ho, MBA (Blackwell Synergy, 2006)
Using an administrative database of dental service records from the Non-Insured Health Benefits (NIHB) program of Health Canada for 1994-2001, the authors set out to test whether regular visitors had lower program expenditures.